Retrospective Analysis of Numerical Pain Rating Scale (NPRS) Scores in Diabetic Neuropathy Patients Receiving Gabapentin and Non-Gabapentin Therapies at an Indonesian Tertiary Hospital - Novianto, Rifky Alif; Hidayati, Hanik Badriyah; Novida, Hermina; Bodová, Klára (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: Diabetic neuropathy is a common complication of diabetes, affecting over half of patients and frequently leading to diabetic neuropathic pain (DNP), which can be difficult to treat. Gabapentin is commonly used as a first-line therapy for DNP and works by modifying calcium channels to reduce pain. This study aimed to evaluate and compare Numerical Pain Rating Scale (NPRS) profiles in DNP patients receiving gabapentin and non-gabapentin therapies at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: This retrospective study analyzed the medical records of 24 DNP patients at Dr. Soetomo General Academic Hospital from January to December 2023. The inclusion criteria comprised patients diagnosed with diabetic neuropathy, according to the International Statistical Classification of Diseases, Tenth Revision (ICD-10) code E11.4, and treated for pain using gabapentin and/or other therapies. Patients with incomplete records or unrelated neuropathic conditions were excluded. The data encompassed NPRS scores, demographics, diabetes mellitus duration, pain characteristics, drug types, doses, and therapy durations. Results: Among 24 patients, the majority were female (54.1%) and over 60 years old (58.3%), with a diabetes duration of 6–10 years (54.1%). Tingling was the most frequently observed symptom (75%). Gabapentin administered as monotherapy (1×300 mg) was the predominant treatment (56.5%) and provided the greatest reduction in NPRS scores (7 points) after 4–12 weeks. Combination therapies showed smaller reductions. Conclusion: Gabapentin used as monotherapy is effective for managing DNP, especially over 4–12 weeks. Patients with long-standing diabetes, particularly older adults, are the most affected and benefit from targeted therapy.   Highlights: 1. This study evaluates the demographic, clinical, and therapeutic profiles of patients with diabetic neuropathic pain, focusing on gabapentin and non-gabapentin therapies.2. Novel insights into the distribution of therapies and numerical pain rating scale (NPRS) scores among patients offer a foundation for optimizing pain management strategies.3. This research contributes to identifying patterns in drug efficacy and therapy duration, particularly with the administration of gabapentin for managing diabetic neuropathic pain.